Efficient Multiplex Genome Editing in Streptomyces via Engineered CRISPR-Cas12a Systems - Zhang, Jun; Zhang, Dan; Zhu, Jie; Liu, Huayi; Liang, Shufang; Luo, Yunzi (Frontiers in Bioengineering and Biotechnology, 2020)
Streptomyces strains produce a great number of valuable natural products. With the development of genome sequencing, a vast number of biosynthetic gene clusters with high potential for use in the discovery of valuable clinical drugs have been revealed. Therefore, emerging needs for tools to manipulate these biosynthetic pathways are presented. Although the clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas 9) system has exhibited great capabilities for gene editing in multiple Streptomyces strains, it has failed to work in some newly discovered strains and some important industrial strains. Additionally, the protospacer adjacent motif (PAM) recognition scope of this system sometimes limits its applications for precise site mutations and insertions. Here, we developed three efficient CRISPR-FnCas12a systems for multiplex genome editing in several Streptomyces strains. Each system exhibited advantages for different applications. The CRISPR-FnCas12a1 system was efficiently applied in the industrial strain S. hygroscopicus, in which SpCas9 does not work well. The CRISPR-FnCas12a2 system was used to delete large fragments ranging from 21.4 kb to 127.6 kb. Additionally, the CRISPR-FnCas12a3 system employing the engineered FnCas12a mutant EP16, which recognizes a broad spectrum of PAM sequences, was used to precisely perform site mutations and insertions. The CRISPR-FnCas12a3 system addressed the limitation of TTN PAM recognition in Streptomyces strains with high GC content. In summary, all the CRISPR-FnCas12a systems developed in this study are powerful tools for precise and multiplex genome editing in Streptomyces strains.